Surface induced vibrational modes in the fluorescence spectra of PTCDA adsorbed on the KCl(100) and NaCl(100) surfaces - Paulheim, A.; Marquardt, C.; Sokolowski, M.; Hochheim, M.; Bredow, T.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (Physical Chemistry Chemical Physics)
We report a combined experiment-theory study on low energy vibrational modes in fluorescence spectra of perylene-3,4,9,10-tetracarboxylic acid dianhydride (PTCDA) molecules.

LiNbO3 electronic structure: Many-body interactions, spin-orbit coupling, and thermal effects - Riefer, Arthur; Friedrich, Michael; Sanna, Simone; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Physical Review B)
The influence of electronic many-body interactions, spin-orbit coupling, and thermal lattice vibrations on the electronic structure of lithium niobate is calculated from first principles. Self-energy calculations in the GW approximation show that the inclusion of self-consistency in the Green function G and the screened Coulomb potential W opens the band gap far stronger than found in previous G0W0 calculations but slightly overestimates its actual value due to the neglect of excitonic effects in W. A realistic frozen-lattice band gap of about 5.9 eV is obtained by combining hybrid density functional theory with the QSGW0 scheme. The renormalization of the band gap due to electron-phonon coupling, derived here using molecular dynamics as well as density functional perturbation theory, reduces this value by about 0.5 eV at room temperature. Spin-orbit coupling does not noticeably modify the fundamental gap but gives rise to a Rashba-like spin texture in the conduction band.

LiTaO3 phonon dispersion and ferroelectric transition calculated from first principles - Friedrich, Michael; Schindlmayr, Arno; Schmidt, Wolf Gero; Sanna, Simone (Physica Status Solidi B)
The phonon dispersions of the ferro‐ and paraelectric phase of LiTaO3 are calculated within density‐functional perturbation theory. The longitudinal optical phonon modes are theoretically derived and compared with available experimental data. Our results confirm the recent phonon assignment proposed by Margueron et al. [J. Appl. Phys. 111, 104105 (2012)] on the basis of spectroscopical studies. A comparison with the phonon band structure of the related material LiNbO3 shows minor differences that can be traced to the atomic‐mass difference between Ta and Nb. The presence of phonons with imaginary frequencies for the paraelectric phase suggests that it does not correspond to a minimum energy structure, and is compatible with an order‐disorder type phase transition.

Strain-induced quasi-one-dimensional rare-earth silicide structures on Si(111) - Timmer, F.; Oelke, R.; Dues, C.; Sanna, S.; Schmidt, Wolf Gero; Franz, M.; Appelfeller, S.; Dähne, M.; Wollschläger, J. (Physical Review B)

Experimental and Theoretical High-Energy-Resolution X-ray Absorption Spectroscopy: Implications for the Investigation of the Entatic State - Vollmers, Nora Jenny; Müller, Patrick; Hoffmann, Alexander; Herres-Pawlis, Sonja; Rohrmüller, Martin; Schmidt, Wolf Gero; Gerstmann, Uwe; Bauer, Matthias (Inorganic Chemistry)

Optical response of the Cu2S2diamond core in Cu2II(NGuaS)2Cl2 - Witte, Matthias; Grimm-Lebsanft, Benjamin; Goos, Arne; Binder, Stephan; Rübhausen, Michael; Bernard, Martin; Neuba, Adam; Gorelsky, Serge; Gerstmann, Uwe; Henkel, Gerald; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

Surface vibrational Raman modes of In:Si(111)(4×1)and(8×2)nanowires - Speiser, E.; Esser, N.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Temperature-Dependent Hole Mobility and Its Limit in Crystal-Phase P3HT Calculated from First Principles - Lücke, Andreas; Ortmann, Frank; Panhans, Michel; Sanna, Simone; Rauls, Eva; Gerstmann, Uwe; Schmidt, Wolf Gero (The Journal of Physical Chemistry B)

Inhomogeneous and Homogeneous Line Broadening of Optical Spectra of PTCDA Molecules Adsorbed at Step Edges of Alkali Halide Surfaces - Paulheim, A.; Marquardt, C.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero; Sokolowski, M. (The Journal of Physical Chemistry C)

Grand canonical Peierls transition in In/Si(111) - Jeckelmann, Eric; Sanna, Simone; Schmidt, Wolf Gero; Speiser, Eugen; Esser, Norbert (Physical Review B)